Des stratégies intégrées durables : savoir écologique traditionnel et gestion adaptative des espaces et des ressources - Mireia Boya Busquet (VertigO)
Since the beginning of the 1990s, Integrated Conservation and Development Projects have offered a functional model of sustainable development, for a specific site within the perspective of a particular project.  The goal is to integrate biological aspects of conservation to the social and economic aspects of development.  The outcomes of the practical results of these strategies show that it has not always been possible to combine conservation and development.In naturally heterogeneous and dynamic contexts, planning must not be a static tool, but instead should evolve with the rhythms of nature and society. With this in mind, the adaptive management approach, based on specific local conditions and community dynamics, integrates design, management, and project follow-through in order to produce a redesign which enables a better adaptation to the context and to the needs of the native population. The acknowledgement of the traditional ecological knowledge of local communities is of vital importance to the proper functioning of strategies wishing to incorporate adaptive management tools. In the African context, this approach can enable the commitment of local actors through their participation in specific projects, learning perspectives, and proper long-term environmental governance.